PRIMARY PULMONARY NON-HODGKIN’S LYMPHOMA - Zhulkevich, I. V.; Uglyar, T. Yu.; Deresh, N. V. (Вісник наукових досліджень, 2015)
Pulmonary non-Hodgkin’s lymphoma is a very rare tumor, which comprises only 0.5 % of all malignancies of lungs. Recommended treatment options include complete surgical excision, surgery followed by radiotherapy or chemotherapy alone but, the optimal therapy remains unclear. The article presents the results of treatment of the patient with primary pulmonary lymphoma, who achieved a partial response after four courses of R-CHOP chemotherapy.